Predicted impacts of climatic change on ant functional diversity and distributions in eastern North American forests. Issue 7 (13th April 2015) - Del Toro, Israel; Silva, Rogério R.; Ellison, Aaron M.; Andersen, Alan
Abstract Aims Climatic change is expected to rearrange species assemblages and ultimately affect organism‐mediated ecosystem processes. We focus on identifying patterns and relationships between common ant species (representing 99% of total ant records) richness and functional diversity; modelling how these patterns may change at local and regional scales in future climatic conditions; and interpreting how these changes might influence ant‐mediated ecosystem processes. Location Forested ecosystems of eastern North America. Methods We used a previously published dataset to evaluate functional diversity at 67 sites in the eastern U.S. and quantified 14 taxonomic, morphometric and natural history traits for 70 common ant species in the region. We used functional diversity metrics, functional groups and species distribution modelling methods to address our aims. We used stacked species distribution models and stacked functional group models to predict species assemblages and functional richness at the 67 sites and at a regional scale for current and future climatic conditions. Results Species richness and functional diversity are positively correlated throughout the region. Under future climate scenarios, species richness and functional group richness were predicted to decrease in southern ecoregions and increase in northern ecoregions. This may be due to increased thermal stress for species in the southern extent of their ranges and increased habitat suitability in the northern ecoregions. Decomposers, arthropod community regulators and seed dispersers are forecast to be the most threatened ant functional groups. Main Conclusions Climate change will likely lead to major changes in ant species richness and functional group richness in the forests of the north‐eastern United States, and this may substantially alter ant‐mediated ecosystem processes and services.